Standardisation of Factor VIII – V. Calibration of the 2nd International Standard for Factor VIII and von Willebrand Factor Activities in Plasma - Heath, A B; Barrowcliffe, T W (Thrombosis and Haemostasis, 1992)
The proposed 2nd International Standard for Factor VIII and von Willebrand Factor activities in plasma, NIBSC code 87/718, was assayed against the 1st IRP, 80/511, and against fresh normal plasma, in 21 laboratories. There were no significant differences between the various assay methods for factor VIII antigen, von Willebrand factor antigen, and von Willebrand factor ristocetin co-factor activity. For factor VIII clotting activity there was a significant difference between the results of one-stage and two-stage assays. Plasma 87/718 has now been established by the WHO Expert Committee on Biological Standardisation as the 2nd IS for factor VIII and vWF in plasma with the following potencies: VIII:C 0.60 IU/ampoule; VIII:Ag 0.91 IU/ampoule; vWF:Ag 0.91 IU/ampoule; vWF/RCo 0.84 IU/ampoule.